Inhibition of Shear-Induced Platelet Aggregation by Xueshuantong via Targeting Piezo1 Channel-Mediated Ca2+ Signaling Pathway - Liu, Lei; Zhang, Qiongling; Xiao, Shunli; Sun, Zhengxiao; Ding, Shilan; Chen, Ying; Wang, Lan; Yin, Xiaojie; Liao, Fulong; Jiang, Lin-Hua; Xue, Mei; You, Yun (Frontiers in Pharmacology, 2021)
XueShuanTong (XST) comprising therapeutically active ginsenosides, a lyophilized extract of Panax notoginseng roots, is extensively used in traditional Chinese medicine to treat ischemic heart and cerebrovascular diseases. Our recent study shows that treatment with XST inhibits shear-induced thrombosis formation but the underlying mechanism remained unclear. This study aimed to investigate the hypothesis that XST inhibited shear-induced platelet aggregation via targeting the mechanosensitive Ca2+-permeable Piezo1 channel by performing platelet aggregation assay, Ca2+ imaging and Western blotting analysis. Exposure to shear at physiologically (1000-2000 s-1) and pathologically related rates (4000-6000 s-1) induced platelet aggregation that was inhibited by treatment with GsMTx-4. Exposure to shear evoked robust Ca2+ responses in platelets that were inhibited by treatment with GsMTx-4 and conversely enhanced by treatment with Yoda1. Treatment with XST at a clinical relevant concentration (0.15 g·L-1) potently inhibited shear-induced Ca2+ responses and platelet aggregation, without altering vWF-mediated platelet adhesion and rolling. Exposure to shear, while resulting in no effect on the calpain-2 expression in platelets, induced calpain-2-mediated cleavage of talin1 protein, which is known to be critical for platelet activation. Shear-induced activation of calpain-2 and cleavage of talin1 were attenuated by treatment with XST. Taken together, our results suggest that XST inhibits shear-induced platelet aggregation via targeting the Piezo1 channel to prevent Piezo1-mediated Ca2+ signalling and downstream calpain-2 and talin1 signal pathway, thus providing novel insights into the mechanism of the therapeutic action of XST on platelet aggregation and thrombosis formation.